Social and financial aspects of the artisanal fisheries of Middle Sao Francisco River, Minas Gerais, Brazil - de Camargo, SAF; Petrere, M. (Blackwell Science, 2001)
The presence or absence of motorized boats, partnerships and multispecies catches characterize the fisheries of Sao Francisco River, Minas Gerais, Brazil. Fishing activity based on 109 interviews, carried out in the wet (high water: February and March) and dry (low water: July and August) seasons, with professional fishermen are described. Aiming to identify the fishery income components, a covariance model was proposed, with the income as the response variable, related to the factors: fishing ground, use of motorized or paddle boat; seasonality; presence of fishing assistant, and the following covariates: capture in weight in the week Frier to the interview, fisherman experience in yrs; and distance (km) travelled for fishing. The results indicated that the main contributions to income were the absence of an engine (because of high price of the fuel), the absence of a partner (because of low capture) and the amount of fish caught by the fishermen.
Keywords: Brazil; commercial fisheries; fishery economy; Sao Francisco River